Clinical application of kangfuxin liquid combined with metronidazole after impacted mandibular third molar extraction - SHOU Wangjin; CHEN Guoyong (Kouqiang hemian waike zazhi)
[Objective:] To evaluate the efficacy of kangfuxin liquid combined with metronidazole in patients with impacted mandibular third molar (IMTM) extraction. [Methods:] A total of 100 patients who underwent IMTM extraction surgery at our hospital from January 2022 to May 2023 were enrolled. They were divided into 3 groups according to different wound treatment regimens: Group A (packing with gelatin sponge) with 34 cases; Group B (kangfuxin liquid + gelatin sponge) with 30 cases; Group C (kangfuxin liquid + metronidazole + gelatin sponge) with 36 cases. The clinical data of the patients were collected. The chi-square test was used to compare granulation tissue coverage rates, dry socket syndrome and the incidence of complications 7 days after surgery. The Kruskal-Wallis test was used to compare the number of patients with limited opening 24 hours after surgery. One-way analysis of variance was used to compare the visual analogue scale (VAS) scores at 24 hours after surgery, degree of facial swelling 24 hours after surgery, healing time of alveolar socket, height of alveolar bone, gray value of bone mineral density, width of alveolar bone, generic quality of life inventory-74 (GQOLI-74) scores. [Results:] Compared with group A, the VAS scores, the degree of facial swelling, the number of patients with grade Ⅲ limited opening 24 hours after the operation in Group B, and the healing time of the alveolar socket, the complete coverage rate of granulation tissue in the alveolar socket 7 days after the operation were significantly improved (P<0.05). Group C was superior to Group A and Group B in all the above indicators (P<0.05). The incidence of dry socket and other complications in Group B were lower than those in group A (P<0.05), while those in Group C were lower than those in both Group A and Group B (P<0.05). Three months after the operation, the alveolar bone heights in all three groups were lower than those before the operation (P<0.05), but those in Group B and Group C were higher than those in Group A (P<0.05). The gray values of bone mineral density were all higher than those before the operation (P<0.05), among which Group B was higher than Group A, and Group C was higher than both Group A and Group B (P<0.05). Seven days after the operation, the GQOLI-74 scores of all three groups were higher than those before the operation (P<0.05). The GQOLI-74 score of Group B was higher than that of Group A, and that of Group C was higher than that of Group A and Group B (P<0.05). [Conclusion:] Kangfuxin liquid combined with metronidazole can effectively promote the recovery of patients after IMTM extraction, prevent the occurrence of complications such as dry socket, and reduce the alveolar bone absorption to some extent.